KONTRIBUSI SELEKSI, KOMPENSASI DAN LOKASI SEKOLAH TERHADAP KINERJA KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN KEBONAGUNG KABUPATEN PACITAN - ISMEDI , GUNTUR (2011)
The purposes of this research are to find out the contribution and the mass contribution of selection, compensation, and the school’s location to the performance of elementary school principal’s and also to find out the variable with the biggest contribution to the performance of elementary school principal’s at District of Kebonagung, Pacitan Residence. This is a quantitative research that using numerical analyzes. This research applied proportional random sampling with 32 persons of respondents, according with Sugiyono’s Sampling for 35 persons of respondents. The author used the questioner as a tool to collect the data and then processed and analyzed by using Regression Equation, Goodness of Fit Test, Estimation of Parameter Test, Normality Test, Heteroskedastisitas Test, Auto Correlation Test and Multi Correlation Test. The result of this research are 1) the simultaneous contribution of selection, compensation, and the school’s location to the performance of elementary school principal’s at District of Kebonagung, Pacitan Residence is 87% with ρ 0,000. 2) the partial contribution of selection to the performance of elementary school principal’s at District of Kebonagung, Pacitan Residence is 0,180 dimension with ρ 0,157. 3) the partial contribution of compensation to the performance of elementary school principal’s at District of Kebonagung, Pacitan Residence is 0,247 dimension with ρ 0,024. 4) the partial contribution of the school’s location to the performance of elementary school principal’s at District of Kebonagung, Pacitan Residence is 0,492 dimension with ρ 0,001. The suggestions of this research are 1) the principal shows gratitude for the accepted compensation and develops the school with quality in order to improve the performance. 2) the school is arranged with interesting, safe composition and design and reachable and also completed with standard school facilities so the educational activities will go fluently. 3) both for the Local Government and the Center One give necessity fund according to the school’s requirement then the school will do intern renovation and rehabilitation and complete its facilities and also support the development of the equipments so the school’s location will be more easy to access, interesting and conducive.